Aerodynamic challenges in running: Understanding headwind and tailwind effects - Beaumont, F.; Polidori, G. (International Journal of Sports Science & Coaching, 2025)
The primary objective of this study was to assess how wind affects metabolic cost of running. A numerical method was employed to investigate aerodynamic forces acting on a runner at three different running speeds (10, 15, and 20 km/h) while experiencing five headwind and tailwind speeds (ranging from 0 to 30 km/h). Additionally, a mathematical model was used to estimate aerodynamic and metabolic power based on both runner and wind speeds. Insights from the numerical investigation highlighted how wind conditions, including speed and direction, alter the turbulent wake behind the runner, ultimately affecting metabolic power requirements. While a 30 km/h tailwind leads to a modest 9% reduction in energy expenditure, a headwind of the same speed results in a substantial 37% increase. In practical terms, running at 13.7 km/h against a 20 km/h headwind imposes the same metabolic demand as running at 19.4 km/h with a 20 km/h tailwind. Furthermore, considering an out and back course, temporary tailwind advantages do not sufficiently offset headwind effects. Thus, this study underscores the critical need for runners to consider weather conditions, especially wind, to effectively manage energy expenditure and optimize performance in competitions or training sessions.